A community informatics framework for enhancing digital capability among mature women: A conceptual model for the trefoil guild Melaka - Sulong, Muhammad Suhaizan; Abdul Aziz, Azlianor; Md. Bohari, Nor Mas Aina; Abdullah, Rosmiza Wahida; Kasim, Amir Syarifuddin; Ahmad, Sabrina; Md. Sanusi, Nurazlina (Society for Science and Education, 2025)
Digital capability has become essential for participation in social, civic, and organisational life, yet mature women continue to experience persistent obstacles that inhibit effective digital engagement. Although Malaysia’s digital transformation initiatives—such as the Malaysia Digital Economy Blueprint (MyDIGITAL)—have expanded infrastructural access, national-level improvements do not automatically translate into sustained capability among older women. Their digital trajectories are shaped more significantly by learning environments, community expectations, organisational routines, and trust in data use practices than by technology availability alone. Within voluntary organisations such as the Trefoil Guild Melaka, members express interest inusing digital tools but face barriers related to unfamiliar interfaces, inconsistent workflows, device limitations, and uncertainty surrounding the sharing, storage, and governance of community-generated data. Drawing on Digital Capability Theory, Community Informatics (CI), Sociotechnical Systems (STS), and emerging literature on Community Data Governance, this paper proposes a Community Informatics–Based Digital Capability Framework tailored to mature women’s learning and participation contexts. This expanded conceptual model explains how social learning environments, sociotechnical alignment, and transparent data practices jointly shape confidence, skill development, digital agency, and sustained organisational participation. The model consolidates theoretical insights, clarifies mechanisms linking community practices to capability outcomes, and offers a foundation for empirical evaluation. Implications for programme design, leadership decisions, and community data stewardship are discussed to support mature women’s empowerment in digitally mediated environments.